Block Liposomes from Curvature-Stabilizing Lipids: Connected Nanotubes, -rods or -spheres - Zidovska, Alexandra (2009)
We report on the discovery of block liposomes, a new class of chain-melted (liquid) vesicles, with membranes comprised of mixtures of the membrane curvature stabilizing multivalent lipid MVLBG2 of colossal charge +16 e and neutral 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine (DOPC). In a narrow MVLBG2 composition range (8-10 mol %), cryo-TEM revealed the block liposomes consisting of distinctly shaped, yet connected, nanoscale spheres, pears, tubes, or rods. Unlike typical liposome systems, where spherical vesicles, tubular vesicles, and cylindrical micelles are separated on the macroscopic scale, within a block liposome, shapes are separated on the nanometer scale. Diblock (pear-tube) and triblock (pear-tube-pear) liposomes contain nanotubes with inner lumen diameter 10-50 nm. Diblock (sphere-rod) liposomes were found to contain micellar nanorods ≈ 4 nm in diameter and several μm in length, analogous to cytoskeletal filaments of eukaryotic cells. Block liposomes may find a range of applications in chemical and nucleic acid delivery and as building blocks in the design of templates for hierarchical structures.